IMPLEMENTATION OF THE RAD METHOD ON THE STUDENT REPORT CARD MANAGEMENT WEBSITE AT SMP ALAM AL-KARIM - Aldo Febrian -; Imam Ahmad; Ryan Halim Faturohman (Jurnal Riset Informatika, 2025)
Alam Al-Karim Junior High School (SMP) is a private educational institution located in Pinang Jaya Village, Kemiling District, Bandar Lampung City, Lampung Province. The academic information system implemented at this school is considered suboptimal, as it still relies on manual processes. This situation has led to several issues, particularly in recording teacher and student data, monitoring student attendance, and managing subject assessments. Therefore, the aim of this study is to develop a website-based academic information system utilizing the Rapid Application Development (RAD) method. The goal is to produce an application capable of providing the expected student report card information. The system testing was conducted through a survey using a Google Form questionnaire, which involved 11 respondents. The survey results indicated an average success rate of 14.7% based on response frequency. The implementation of a website-based report card management system has accelerated the presentation of academic information at SMP Alam Al-Karim, as evidenced by a 7.35% agreement frequency among respondents. Furthermore, data management processes have become more efficient, contributing to improved time efficiency and report generation effectiveness.